Public Communication Observatory: research, criticism and citizenship (Comunicação & Inovação, 2017)
The purpose of this article is reflect about the process of creation, construction and operation of the project Observatório da Comunicação Pública (Obcomp) based on theoretical-practical perspectives that relate themes of public interest, citizenship and communication in Brazilian democracy. Headquartered in Programa de Pós-Graduação em Comunicação e Informação (PPGCOM) from Universidade Federal do Rio Grande do Sul (UFRGS), Brazil, the conceptual axis of the Obcomp is public communication. In this direction, it's constitute of debate and criticism, since it captures, classifies and makes available information about state communication and news of public interest, besides to accompany public broadcasting.
Keywords: Public Communication; Observatories; Public Interest